EFFECTIVENESS OF STELLARIUM APPLICATION IN ENHANCING STUDENT'S UNDERSTANDING: ASTRONOMY CONCEPTS IN PHYSICS EDUCATION - Nasution, Lia Afriyanti; Khairiah, Khairiah; Siregar, Juliandi; Destini, Rita; Kurniawan, Chandra; Rusli, Roslinda binti (Universitas Labuhanbatu, 2025)
Purpose -This study aims to address the challenges of teaching astronomy in higher education, particularly in institutions with limited observational infrastructure and urban light pollution. The purpose of this research is to investigate the effectiveness of Stellarium, a digital planetarium application, in enhancing students' conceptual understanding of astronomy concepts in Physics Education.Methodology - A quasi-experimental research design was employed, utilizing a pretest-posttest control group format. The sample consisted of 30 undergraduate students enrolled in the astronomy course, who were purposively selected and divided into an experimental group and a control group. The research procedure involved the development of Stellarium-integrated instructional materials, the implementation of teaching interventions, and the administration of pretests and post-tests to assess conceptual understanding. Additional instruments included a questionnaire to capture students' perceptions and documentation of classroom activities. Data were analyzed using paired sample t-tests, independent sample tests, and descriptive statistics.Findings - The results of the initial and final trials showed a significant increase in the experimental group's understanding of astronomical concepts. In contrast, the control group showed minimal improvement. The findings revealed a significant improvement in the experimental group's test scores, with an average gain of 16.6 points (p < 0.05). Students also expressed highly positive perceptions of Stellarium in terms of visual appeal, ease of use, learning motivation, and comprehension of celestial motion. These results suggest that Stellarium is an effective pedagogical tool for enhancing conceptual understanding of astronomy and fostering student engagement.Contribution- The study contributes to the growing body of research on simulation-based learning and offers practical insights into integrating digital technologies in science education, particularly in resource-constrained institutions. It also offers a model for adapting global digital tools to local educational contexts, thereby supporting curriculum innovation in Indonesian higher education.